2015
DOI: 10.1002/jsfa.7466
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a stable humic–urease complex: application to barley seed encapsulation for improving N uptake

Abstract: Seed encapsulation with urease could substantially contribute to enhancing plant N nutrition in the early stages of seedling establishment. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
9
0
2
Order By: Relevance
“…Seed encapsulation with the enzymes in the immobilized form resulted in a higher enzyme coating stability (Figure 1), which can be explained by the association of the studied enzymes to the humic support. Many researchers (Mvila et al, 2016;Dong et al, 2008;Li et al, 2013) have reported increased stability of proteins bound to humic substances.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Seed encapsulation with the enzymes in the immobilized form resulted in a higher enzyme coating stability (Figure 1), which can be explained by the association of the studied enzymes to the humic support. Many researchers (Mvila et al, 2016;Dong et al, 2008;Li et al, 2013) have reported increased stability of proteins bound to humic substances.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the coating of barley seeds with alkaline phosphatase, free and immobilized in humates, improved the use of soil P by plants (Pilar et al, 2009;Pilar-Izquierdo et al, 2012, 2013. Mvila et al (2016) found that barley seed coating with urease and humic-urease-complexes significantly increased the plant N uptake.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Серед важливих елементів технології вирощування є застосування передпосівної обробки насіння гуматами, що особливо актуально через збільшення частоти ризиків, пов'язаних із виникненням стресових факторів [4,5,6]. Гумінові речовини позитивно впливають на динаміку наростання кореневої маси та формування фотосинтетичного апарату впродовж етапів розвитку рослин [7,8,9].…”
Section: вступunclassified